Assistance in Establishing a Garbage Bank for Urban Communities Based on Community Assets, in Wonokusumo Kidul Surabaya - Wahanani Mawasti (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
This study aims to describe the stages of assisting the establishment of waste banks in urban areas. This is based on the existence of problems in urban areas, especially in the field of environment (settlements) and economy. The approach used in the implementation of mentoring is community asset-based community development. The role of the companion as a facilitator in the process of social change in the community. The results showed the success of community empowerment in urban areas by utilizing community assets. This success took the form of the establishment of the "Songolikoer" Waste Bank. The establishment of a Waste Bank is a form of optimizing tangible and intangible community assets. Support for community participation in the implementation of the community asset-based empowerment phase has an important role to bring about change in society. The community asset-based community development approach can be integrated with other approaches such as SWOT analysis or partnerships..